A variable gene family encoding nodule-specific cysteine-rich peptides in pea (Pisum sativum L.) - Zorin, Evgeny A.; Kliukova, Marina S.; Afonin, Alexey M.; Gribchenko, Emma S.; Gordon, Mikhail L.; Sulima, Anton S.; Zhernakov, Aleksandr I.; Kulaeva, Olga A.; Romanyuk, Daria A.; Kusakin, Pyotr G.; Tsyganova, Anna V.; Tsyganov, Viktor E.; et al. (Frontiers in Plant Science, 2022)
Various legume plants form root nodules in which symbiotic bacteria (rhizobia) fix atmospheric nitrogen after differentiation into a symbiotic form named bacteroids. In some legume species, bacteroid differentiation is promoted by defensin-like nodule-specific cysteine-rich (NCR) peptides. NCR peptides have best been studied in the model legume Medicago truncatula Gaertn., while in many other legumes relevant information is still fragmentary. Here, we characterize the NCR gene family in pea (Pisum sativum L.) using genomic and transcriptomic data. We found 360 genes encoding NCR peptides that are expressed in nodules. The sequences of pea NCR genes and putative peptides are highly variable and differ significantly from NCR sequences of M. truncatula. Indeed, only one pair of orthologs (PsNCR47/MtNCR312) has been identified. The NCR genes in the pea genome are located in clusters and the expression patterns of NCR genes from one cluster tend to be similar. These data support the idea of independent evolution of NCR genes by duplication and diversification in related legume species. We also described spatio-temporal expression profiles of NCRs and identified specific transcription factors binding sites in promotors of ‘early’ and ‘late’ NCR genes. Further, we studied the expression of NCR genes in nodules of Fix- mutants and predicted potential regulators of NCR gene expression, one among them being the transcription factor ERN1 involved in early steps of nodule organogenesis. In general, this study contributes to understanding the functions of NCRs in legume nodules and contributes to understanding of the diversity and potential antibiotic properties of pea nodule-specific anti-microbial molecules.